2014
DOI: 10.2217/fon.14.187
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Breast Cancer Treatment as a Sensitive Setting for Trastuzumab Biosimilar Development and Extrapolation

Abstract: Treatment of patients with neoadjuvant breast cancer represents a sensitive setting for establishing biosimilarity of efficacy and immunogenicity. tpCR is a sensitive end point in this setting to establish biosimilarity between a biosimilar candidate and its reference product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
0
31
0
2
Order By: Relevance
“…For example, in scientific conferences and in recent literature, it is discussed whether, for biosimilar mAbs for breast cancer, neoadjuvant treatment should be favored over the metastatic setting, or whether, for biosimilar rituximab, extrapolation from a nononcological indication (rheumatoid arthritis) to an oncological indication (lymphoma) should be allowed. 50,51 Although the latter appears to be challenging, extrapolation may be possible, provided that all active moieties of the antibody molecule are rigorously tested and compared, and their functions (eg, that are different in the various lymphoma indications of rituximab) are established to be the same. Generally, all biosimilar developments-irrespective of whether they use the model systems that are emerging in clinical literature-have been critically discussed with regulators within scientific advice procedures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in scientific conferences and in recent literature, it is discussed whether, for biosimilar mAbs for breast cancer, neoadjuvant treatment should be favored over the metastatic setting, or whether, for biosimilar rituximab, extrapolation from a nononcological indication (rheumatoid arthritis) to an oncological indication (lymphoma) should be allowed. 50,51 Although the latter appears to be challenging, extrapolation may be possible, provided that all active moieties of the antibody molecule are rigorously tested and compared, and their functions (eg, that are different in the various lymphoma indications of rituximab) are established to be the same. Generally, all biosimilar developments-irrespective of whether they use the model systems that are emerging in clinical literature-have been critically discussed with regulators within scientific advice procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Jackisch et al [13 ]presented in an evaluation of the sensitivity of endpoints for eBC and mBC in similarity studies of trastuzumab RP and biosimilars that the shorter-term endpoint of ORR for the measurement of equivalence led to a substantial difference in long-term PFS despite prior findings suggesting ORR being a surrogate for PFS in mBC. They found that at an equivalence margin of 10% for ORR was associated with a difference in PFS of 3.2 months.…”
Section: Clinical Developmentmentioning
confidence: 99%
“…In the single-dose study, anti-drug antibodies (ADA) were identified by day 29 in all animals administered PF-05280586 or rituximab-EU, and they persisted through day 85, the last day they were tested for. In the repeat-dose study, ADA were detected on day 121 in 50% of Contrary to the initial biosimilars used in supportive care, trastuzumab is an anticancer drug, a specific targeted agent and thus it appears that the neoadjuvant setting may be the right choice to compare a trastuzumab biosimilar with the originator to assess efficacy and safety [Jackisch et al 2015]. Several trastuzumab biosimilars are either ready to be commercialized or are in clinical development [Hurst et al 2014].…”
Section: Pf-05280586mentioning
confidence: 99%